1992
DOI: 10.1002/clc.4960151029
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular arrhythmias and the autonomic tone in patients with mitral valve prolapse

Abstract: Summary: The aim of this study was to evaluate a possible relation between the autonomic tone determined by daily urine catecholamine excretion and the incidence of ventricular arrhythmias (VA) in patients with mitral valve prolapse (MVP). The study included 53 patients (31 women and 22 men) aged 19-52 years (mean age 32.7). The diagnosis of MVP was based on medical history, physical examination, and echocardiography. Cardiac arrhythmias were detected by Holter monitoring and classified according to Lown grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…These contact lesions may predispose to fibrotic change but may also serve to trigger premature contractions resulting in ventricular arrhythmias . As such, the predisposition to arrhythmia in certain MVP patients appears to stem from a combination of mechanical effects triggering premature beats and abnormal substrate related fibrosis . To our knowledge, however, the detailed electrophysiological mechanisms underlying such arrhythmias in BiMVP have not been reported.…”
Section: Discussionmentioning
confidence: 96%
“…These contact lesions may predispose to fibrotic change but may also serve to trigger premature contractions resulting in ventricular arrhythmias . As such, the predisposition to arrhythmia in certain MVP patients appears to stem from a combination of mechanical effects triggering premature beats and abnormal substrate related fibrosis . To our knowledge, however, the detailed electrophysiological mechanisms underlying such arrhythmias in BiMVP have not been reported.…”
Section: Discussionmentioning
confidence: 96%
“…Further, QT dispersion was found to be related to the degree of prolapse and leaflet thickness, providing a mechanical correlation for electrical disturbances in MVP 22 . A role for increased autonomic tone has been proposed with relatively higher catecholamine excretion in MVP patients with ventricular arrhythmia 23 . Wilde and colleagues performed detailed mapping studies on a patient with MVP and VT and concluded that delayed afterdepolarization-induced triggered activity was the mechanism, with stretch and fibrosis of the papillary muscles contributing to the origin of the arrhythmia 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Increased autonomic tone is another proposed mechanism of ventricular arrhythmias, as are abnormal catecholamine regulation, increased catecholaminergic state, and baroreflex modulation in patients with MVP [27,28]. Previous studies have shown increased catecholaminergic activity to be associated with repolarization abnormalities and ventricular arrhythmias [9]. Several reports showed alterations in ventricular repolarization, such as increased QT and QTc dispersions, in MVP patients [29,30].…”
Section: Discussionmentioning
confidence: 97%
“…The exact mechanisms causing ventricular arrhythmias remain elusive. Structural abnormalities of the mitral valve leading to mechanical triggering and abnormalities of the autonomic nervous system are considered to be the underlying conditions of ventricular arrhythmias [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%